2007
DOI: 10.1016/j.brainres.2006.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Role of GABAergic antagonism in the neuroprotective effects of bilobalide

Abstract: Bilobalide, a constituent of Ginkgo biloba, has neuroprotective properties. Its mechanism of action is unknown but it was recently found to block GABA A receptors. The goal of this study was to test the potential role of a GABAergic mechanism for the neuroprotective activity of bilobalide. In rat hippocampal slices exposed to NMDA, release of choline indicates breakdown of membrane phospholipids. NMDA-induced choline release was almost completely blocked in the presence of bilobalide (10 μM) and under low-chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Although the (Mo) constituent(s) demonstrated antagonistic effects, potential therapeutic effects of (Mo) and its constituent(s) need to be investigated further. Bilobalide, a single natural product sesquiterpene trilactone derived from Ginkgo biloba, which has been used for the treatment of AD displayed a similar inhibitory effect on GABA A receptor as seen herein, and also neuroprotective effects, presumably through other mechanisms [21], again similar to that observed for Melissa essential oil. Electrophysiological studies have shown that (Mo) depress membrane excitability at low concentrations [18], despite this effect upon GABA A receptor at higher concentrations.…”
Section: Effects Of Melissa Essential Oil (Mo) On Neuronal Viabilitysupporting
confidence: 77%
“…Although the (Mo) constituent(s) demonstrated antagonistic effects, potential therapeutic effects of (Mo) and its constituent(s) need to be investigated further. Bilobalide, a single natural product sesquiterpene trilactone derived from Ginkgo biloba, which has been used for the treatment of AD displayed a similar inhibitory effect on GABA A receptor as seen herein, and also neuroprotective effects, presumably through other mechanisms [21], again similar to that observed for Melissa essential oil. Electrophysiological studies have shown that (Mo) depress membrane excitability at low concentrations [18], despite this effect upon GABA A receptor at higher concentrations.…”
Section: Effects Of Melissa Essential Oil (Mo) On Neuronal Viabilitysupporting
confidence: 77%
“…One investigation examined further the GABA‐A mechanisms of action for bilobalide in rat hippocampal tissue and reported a blocking of GABA‐induced chloride uptake in these cells at low potency. In turn, GABA was found to partially antagonise bilobalide's inhibitory actions (Kiewert et al, ). One recent study reported that both bilobalide and ginkgolide B selectively inhibited structurally‐varied GABA‐A positive modulator agent actions when tested in Xenopus oocytes (Ng, Duke, Hinton, & Johnston, ).…”
Section: Resultsmentioning
confidence: 99%
“…Bilobalide has been found to improve mitochondrial activity and to preserve ATP levels during ischemia [3,13]. We have investigated interactions of bilobalide with amino acid neurotransmitters such as GABA, glycine, and glutamate [14,15]. Very recently, several constituents of EGb761 were implied in the induction of heme oxygenase-1 in ischemic neurons [16].…”
Section: Introductionmentioning
confidence: 99%